Difficult Conversations: Teaching Medical Oncology Trainees Communication Skills One Hour at a Time - Epner, Daniel E. (Acad Med, 2014)
Difficult conversations about prognosis, end of life, and goals of care arise commonly in medical oncology practice. These conversations are often highly emotional. Medical oncologists need outstanding, patient-centered communication skills to build trust and rapport with their patients and help them make well-informed decisions. Key skills include exploring patients’ perspectives, responding to emotion with empathy, and maintaining mindfulness during highly charged conversations. These skills can be taught and learned. Most previously described communication skills training curricula for oncology providers involve multiday retreats, which are costly and can disrupt busy clinical schedules. Many curricula involve a variety of oncology providers, such as physicians and nurses, at various stages of their careers. The authors developed a monthly, one-hour communication skills training seminar series exclusively for physicians in their first year of medical oncology subspecialty training. The curriculum involved a variety of interactive and engaging educational methods, including sociodramatic techniques, role-play, reflective writing, and Balint-type case discussion groups. Medical oncologists in their second and third years of training served as teaching assistants and peer mentors. Learners had the opportunity to practice skills during sessions and with patients between sessions. Learners acquired important skills and found the curriculum to be clinically relevant, judging by anonymous surveys and anonymous responses on reflective writing exercises. Results from the current curriculum are preliminary but lay the foundation for enhanced and expanded communication skills training programs in the future.